A high-cholesterol diet enriched with polyphenols from Oriental plums (Prunus salicina) improves cognitive function and lowers brain cholesterol levels and neurodegenerative-related protein expression in mice. Issue 10 (13th April 2015) - Kuo, Ping-Hui; Lin, Ching-I; Chen, Yue-Hwa; Chiu, Wan-Chun; Lin, Shyh-Hsiang
Abstract : Ageing accompanied by a decline in cognitive performance may be a result of the long-term effects of oxidative stress on neurologic processes. It has been shown that high-cholesterol contents in the blood and brain may lead to the deposition of the β-amyloid (Aβ) protein in the brain, which damages brain cells. The present study was designed to observe the effect of polyphenol-rich Oriental plums on cognitive function and cerebral neurodegeneration-related protein expression in mice that were fed a high-cholesterol diet for 5 months. The study consisted of four groups: the control (Ctrl) group, which was fed the American Institute of Nutrition (AIN)-93M diet; the high cholesterol (HC) group, which was fed the AIN-93M diet with 5 % cholesterol; the high cholesterol+low Oriental plum (LOP) group, which was fed the AIN-93M diet with 5 % cholesterol and 2 % Oriental plum powder; and the high cholesterol+high Oriental plum (HOP) group, which was fed the AIN-93M diet with 5 % cholesterol and 5 % Oriental plum powder. Measurements of cognitive function were assessed using the Morris water maze, and the mRNA expression of cholesterol hydroxylase ( Cyp46 ), Aβ and β-secretase 1 ( BACE1 ) were analysed. The results showed that cholesterol concentrations in both the blood and the brain were significantly higher in the HC group than in the Ctrl and HOP groups at the end of the trial. The high-cholesterol diet per se produced significant cognitive deficits, which were accompanied by a significantly increased mRNA expression of Cyp46, BACE1, Aβ and 24-hydroxycholesterol in the brain cortex and hippocampus. However, all of these variables were non-significantly increased in the HOP group as compared to the Ctrl group. In conclusion, incorporating polyphenol-enriched Oriental plum into a high-cholesterol diet can ameliorate some of the symptoms of neurodegenerative conditions.